Bilingualism in persons with intllectual disabilities - María José Rabazo Méndez; Mercedes Gómez Acuñas (INFAD, 2018)
The issue of bilingualism in students with intellectual disabilities has been little explored, whether it is simultaneous bilingualism or sequential bilingualism; however, to live in a society marked by phenomena such as globalization, intercommunication and international mobility, in a society that is linguistically and culturally diverse, to attend educational centers where the introduction of a different language as a vehicular language for learning is usual. together with the empirical evidence on the cognitive benefits derived from an additive bilingualism are sufficient reasons to be interested in the possibilities of this group learning a second language. Purpose. Analyze the available information on the ability of people with intellectual disabilities to learn more than one language (L2). Design. Theoretical research. Narrative review. Material: Eleven research articles have been reviewed and we have had access to different forums where professionals and families tell us about the ability of people with intellectual disabilities to learn a L2. Results. The period studied covers from 1991 to 2016; Of the ten articles, two empirical study, a systematic review, a narrative review and seven case descriptions have been found. Conclusions. Taking into account the scarce representativeness of the information found, as can be seen from the results obtained, it can be said that: people with intellectual disabilities can learn two or more languages; they will have corresponding difficulties in regard to various language components and they will exhibit corresponding delays in the development of L2 and L1 learning; the learning of an L2 does not mean a delay in the learning and development of its L1; bilingual children with intellectual disabilities use their dominant language as well as monolingual children for the same level of development.